Performance Analysis and Company Strategy Using MBCfPE Method and SWOT Analysis at PT. X HC and GA Unit - Putri Suryaninggar, Ega Nandita; Iriani, Iriani (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
This research aims to analyze the performance of the HC and GA work unit in relation to the overall performance of the company to enhance its competitiveness. Additionally, it provides valuable input to the company's management as improvement proposals to optimize the performance of the HC and GA work unit, enabling it to contribute optimally to the company's objectives.The study employed the Proportionate Stratified Random Sampling technique with a sample size of 32 employees. It utilized the Malcolm Baldrige Criteria for Performance Excellence method to assess the company's performance and conducted a SWOT analysis to provide strategic recommendations.The study employed the Proportionate Stratified Random Sampling technique with a sample size of 32 employees. It utilized the Malcolm Baldrige Criteria for Performance Excellence method to assess the company's performance and conducted a SWOT analysis to provide strategic recommendations.The novelty of this study lies in the holistic integration of the MBCfPE method and SWOT analysis to provide a comprehensive view of the company's performance and strategies.This research offers profound insights into the performance of PT. Semen Indonesia Pabrik Tuban's HC&GA work unit, as well as suitable strategies to optimize success by integrating the MBCfPE method and SWOT analysis.